Does capital regulation matter for bank behavior? Evidence for German savings banks - Frank Heid; Daniel Porath; Stéphanie Stolz (Kiel Institute for World Economics (IfW), 2003)
The aim of this paper is to assess how German savings banks adjust capital and risk under capital regulation. We estimate a modified version of the model developed by Shrieves and Dahl (1992). In comparison to former research, we impose fewer restrictions with regard to the impact of regulation on capital and risk adjustments. Besides, we complement our analysis with dynamic panel data techniques and a rolling window approach. We find evidence that the coordination of capital and risk adjustments depends on the amount of capital the bank holds in excess of the regulatory minimum (the so-called capital buffer). Banks with low capital buffers try to rebuild an appropriate capital buffer by raising capital and simultaneously lowering risk. In contrast, banks with high capital buffers try to maintain their capital buffer by increasing risk when capital increases.
Keywords: G28; G21; 330; bank regulation; risk taking; bank capital; Sparkasse; Bankrisiko; Eigenkapitalvorschriften; Bilanzstrukturmanagement; Schätzung; Deutschland